PARTISIPASI DAN PERAN PEREMPUAN DALAM PARTAI POLITIK - St. Habibah (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2015)
Participation of women in political parties is quite high in managerial, organizational meetings, voting, campaigns, political discussions and public meetings that have been carried out by many existing political parties. However, the main problem in woman’s political activities is the appearance of injustice as a result of the disparities between women's political rights and participation at one side and the political rights and roles of men on the other side. Recently, the role of women in political parties is just ordinary member of an organization. Several informants say that women who are members of an organization mostly do not have much experience in organizing and do not possess courageous characteristics as men generally do. For this reason, many working programs proposed by women are not accepted and implemented into the existing political world. The position of women in political parties is generally stereotyped. The factors that affect women's involvement in political parties are: the influence of their educational background, which mainly determines the activeness of women in their involvement as the member of political party, because all the tasks entrusted to women can be implemented due to the education possessed by these women. This means that there is a relevancy between their educational background and their duties. Some constraints experienced by women in political parties are based on several issues including educational background, jobs, gender equality and justice, domestic role, patriarchal culture, religion, and family relationships.